2022
DOI: 10.1109/jtehm.2022.3207825
|View full text |Cite
|
Sign up to set email alerts
|

A Precision Health Service for Chronic Diseases: Development and Cohort Study Using Wearable Device, Machine Learning, and Deep Learning

Abstract: This paper presents an integrated and scalable precision health service for health promotion and chronic disease prevention. Continuous real-time monitoring of lifestyle and environmental factors is implemented by integrating wearable devices, open environmental data, indoor air quality sensing devices, a location-based smartphone app, and an AI-assisted telecare platform. The AI-assisted telecare platform provided comprehensive insight into patients' clinical, lifestyle, and environmental data, and generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Wrapper-based feature selection can be completed by ranking the features in terms of relative importance using a ML model (such as decision trees or random forests) [88,101,113]. We identified a handful of feature ranking methods that include two stepwise regression techniques: Forward Selection and Backwards Elimination [29,36,52,[114][115][116], as well as Recursive Feature Selection (RFE) [30,117]. Forward selection starts the modelling process with zero features and adds a new feature to the model incrementally, each time testing for statistical significance.…”
Section: Wrapper Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wrapper-based feature selection can be completed by ranking the features in terms of relative importance using a ML model (such as decision trees or random forests) [88,101,113]. We identified a handful of feature ranking methods that include two stepwise regression techniques: Forward Selection and Backwards Elimination [29,36,52,[114][115][116], as well as Recursive Feature Selection (RFE) [30,117]. Forward selection starts the modelling process with zero features and adds a new feature to the model incrementally, each time testing for statistical significance.…”
Section: Wrapper Methodsmentioning
confidence: 99%
“…When similar hyperparameter tuning processes can be used for different ML algorithms for different datasets, researchers can then identify the optimal ML model. Among the selected studies, 25 discussed which hyperparameters were considered for their models [23,24,34,43,44,46,53,69,73,86,87,94,95,[107][108][109][110]114,138,158,159,[181][182][183][184], of which one stated they used the default hyperparameters of the models [69]. Only nine studies discussed how they selected or optimized their hyperparameters.…”
Section: Model Hyperparametersmentioning
confidence: 99%
“…They offer accurate, measurable precision medicine to improve health and prevent chronic disease. Similarly, smartphone app integration enables real-time monitoring of lifestyle and environmental parameters [8]. Therefore, the OCI-DBN method may compare the trial findings with other cuttingedge methods to enhance the system's performance [9].…”
Section: Literature Surveymentioning
confidence: 99%
“…Several studies have suggested that wearable devices can provide more reliable, detailed data on human activities and exposure characteristics, 4,5 providing an effective way to assess health risks and facilitate further interventions 6,7 . For example, wearable devices can monitor health indicators such as weight, fat, blood sugar, and blood pressure to detect the risks of metabolic diseases early and help patients effectively control their condition.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that wearable devices can provide more reliable, detailed data on human activities and exposure characteristics, 4 , 5 providing an effective way to assess health risks and facilitate further interventions. 6 , 7 For example, wearable devices can monitor health indicators such as weight, fat, blood sugar, and blood pressure to detect the risks of metabolic diseases early and help patients effectively control their condition. Moreover, these devices can deliver real‐time condition data of patient changes and identify potential risks in a timely manner to provide clinical doctors with customized treatment plans to effectively improve their patients’ health.…”
Section: Introductionmentioning
confidence: 99%